Assessing Effect of The Factors that Influence Financial Reporting Information Quality - Bawono, Icuk Rangga; Suroso, Agus; Yuniarso, Gema Puja (AKRUAL: JURNAL AKUNTANSI, 2021)
A particular form of information used as user requirements for the process of decision-making. A qualified information is important for interested party who used that information to reduce uncertainty and knowledge upgrade on the specific concern areas. By considering information is a wishful move for doing an activity. The information quality of financial statements that the government publishes in public has to meet standards to be trusted and used by people so people could rely on for making a decision. The objective to do this research is to verify relationship betweenÂ  human resources competency, accounting information system, and internal control on accounting information quality of government financial statements. The paradigm of this research is quantitative research. The sampling method used is a nonprobability sampling (saturated sampling) with quota. The research was conducted by distributing questionnaires to 43 respondents who are SIMDA operator on the government work unit of Central Sulawesi Provincial Government. Multiple linear regression analysis used to analyze data. The results showed that human resources competency, accounting information system, and internal control have a positive effect on the quality of financial reporting information in Central Sulawesi Provincial Government.Â